A diffusion rls scheme for distributed estimation over adaptive networks - Cattivelli, F.S.; Lopes, C.G.; Sayed, A.H. (2007 IEEE 8th Workshop on Signal Processing Advances in Wireless Communications, 2007)
We consider the problem of distributed estimation in adaptive networks where a collection of nodes are required to estimate in a collaborative manner some parameter of interest from their measurements. The centralized solution to the problem uses a fusion center, thus requiring a large amount of energy for communication. We propose a diffusion recursive least-squares algorithm where nodes need to communicate only with their closest neighbors. The algorithm has no topology constraints, and requires no transmission or inversion of matrices, therefore saving in communications and complexity. We show that the algorithm is stable and analyze its performance comparing it to the centralized global solution.